Effects of algae growth on cadmium remobilization and ecological risk in sediments of Taihu Lake. (May 2016) - Ni, Lixiao; Li, Dandan; Su, Lili; Xu, Jiajun; Li, Shiyin; Ye, Xiang; Geng, Hong; Wang, Peifang; Li, Yi; Li, Yiping; Acharya, Kumud
Abstract: Indoor simulation experiment with 2.76 L microcosms using sediment from Taihu Lake were conducted to investigate the relationship between algae bloom and heavy metals release into a lake aquatic environment. The results showed that Microcystic aeruginosa (M. aeruginosa) growth can enhance cadmium (Cd) mobilization from sediments to overlying water due to increasing pH and DO content of overlying water and changing the redox condition of surface sediment (0–2 cm) from weak oxidation to weak reduction. The dissolved Cd concentration in overlying water can be decreased during algal growth process. The remobilization of Cd from sediment can effectively reduce the ecological risk of total Cd in sediments. The results of this study showed that both Igeo and Er i can be used to effectively evaluate the ecological risk of heavy metal Cd in different fractions. Highlights: Heavy metals pollution in sediments can pose a serious risk to the ecosystems. Algal growth can change pH, DO and redox condition of water and sediment. Algal growth can improve Cd migration from sediments to the overlying water. Algal growth can reduce the ecological risk of Cd in sediments. Igeo and Er i can be used to effectively evaluate the ecological risk of Cd in different fractions.